Analisis Hukum Perjanjian Penyembuhan Kepada Pasien Dari Penyelenggara Praktik Pengobatan Tradisional - Rissa Afni Martinouva (Law Faculty of Universitas Bandar Lampung, 2018)
The organization of traditional medicine practices is an alternative healing path besides medical methods. The practice of traditional medicine must be supported by a health law device intended to provide legal certainty and protection for community members as patients and traditional treatment providers. This study is intended to find out the regulations that protect the organization of traditional medical practices and the forms of healing agreements provided by providers of traditional medical practices for patients. The research method used is normative by reviewing regulations, literature studies and observations of traditional medicine. The implementation of traditional medical practices is supported by several regulations including the Minister of Health Decree No. 1076 / MENKES / SK / VII / 2003 concerning Traditional Medicine Administrators and Law No. 36 of 2009 concerning Health. The health law instrument is intended to provide legal certainty and protection for community members as patients and traditional treatment providers. The traditional treatment agreement is clear that if carried out in accordance with the procedures specified by law is a legal agreement and binds the parties to traditional healers and patients. The type of agreement used by traditional healers and patients is a healing agreement (therapeutic agreement). A therapeutic agreement is a term of agreement that deals with a doctor that also applies to traditional healing staff as health care providers. Healing agreements within the scope of traditional medicine are not currently supported by clarifying the legal requirements of the agreement specifically.